Corrigendum to “Assessment of the breakdown products of solar/UV induced photolytic degradation of food dye tartrazine” [Food and Chemical Toxicology 68 (2014) 307–315](S0278691514001549)(10.1016/j.fct.2014.03.025) - dos Santos, Tuane Cristina [UNESP]; Zocolo, Guilherme Julião [UNESP]; Morales, Daniel Alexandre; de Aragão Umbuzeiro, Gisela; Boldrin Zanoni, Maria Valnice [UNESP] (Elsevier, 2017)
The authors regret ‘Although by-products were formed, the Salmonella/microsome mutagenicity assay performed for both, the dye solution at a dose of 5.34 μg/plate and the solutions obtained after exposure to UV irradiation, did not present mutagenic activity for TA98 and TA100 with and without S9.’ The authors would like to apologise for any inconvenience caused.